The Use of Small Group Discussion and Snowballing Techniques: An Effort to enhance EFL Studentsâ Self âEfficacy and Speaking Skill - Silvana, Ade; Kustati, Martin; Darmayanti, Darmayanti (AT-TALIM, 2018)
This paper is aimed at discussing on Small Group Discussion and Snowballing techniques enhance studentsâ self-efficacy and speaking skill on hortatory exposition text at class XI State Islamic Senior High School 1 Padang in academic year 2016/2017. The experimental research type and factorial design were used to conduct the research. Two groups of experimental classes, who were cluster randomly selected, were taught by different techniques. First group was taught by Snowballing and second one was taught by Small Group Discussion. Both groups were given post-test after they got different treatments to find out whether both two groups shown differences and the effectiveness of the different treatments. Speaking test and questionnaires were used to collect the data. The t- test and two ways ANOVA were used to analyze the data. The results of the research have shown that students who were taught by snowballing were better than those who were taught by small group discussion in speaking skill on hortatory text. The studentsâ self-efficacy in speaking skill that was taught by snowballing was higher than that was taught by small group discussion. The students with high self-efficacy got higher speaking score than students with low self-efficacy. It is concluded that Snowballing technique gives more significant effect on students self-efficacy in speaking skill than Small Group discussion one. It is recommended that English teachers have to use Snowballing technique to increase studentsâ self-efficacy and skill in speaking.